Anatomical variation findings of the paranasal sinuses based on CT scans in rhinosinusitis - Thelim, Adeline; Pulungan, Ica Yulianti; Nasution, Ikhwanul Hakim; Rahmi, Clairine Altin Nur (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Rhinosinusitis is an inflammation of the paranasal sinuses and nasal mucosa that occurs due to bacterial, viral, fungal infections, allergens, or autoimmune conditions with signs and symptoms such as nasal congestion, runny nose, facial pain, and decreased olfactory ability, with causes such as host factors that are divided into systemic and local (such as anatomical abnormalities) as well as environmental factors such as viral or bacterial infections and allergen exposure. Anatomical variations in the sinonasal area can cause impaired drainage and ventilation to obstruction of the osteomeatal complex which ultimately causes and even exacerbates inflammation of the sinus mucosa, examples of anatomical variations such as septal deviation, agger nasi cells, concha bullosa, haller cells, onodi cells, and others, with the radiological modality widely used is CT - Scan. This study aimed to identify anatomical variations in rhinosinusitis cases based on CT scan examination results. This study is descriptive and uses a total sampling technique. A total of 53 samples were taken, with rhinosinusitis as the main diagnosis. Subsequently, a frequency distribution test was conducted. It was found that 45 samples had no anatomical variation and eight samples had anatomical variations in the form of septal deviation. The results showed that the anatomical variation found in rhinosinusitis patients at RSUD Dr. Pirngadi had a septal deviation of as many as eight samples (15.1%).